Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/ccm.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of Intracranial Pressure Monitoring in Acute Liver Failure

Abstract: Objective To determine if intracranial pressure (ICP) monitor placement in acute liver failure (ALF) patients is associated with significant clinical outcomes. Design Retrospective multicenter cohort study. Setting Academic liver transplant centers comprising the US ALF Study Group. Patients and participants Adult critically ill ALF patients presenting with Grade III/IV hepatic encephalopathy (n=629) prospectively enrolled between 3/2004 to 8/2011. Intervention ICP monitored (ICPM; n=140) vs. non-monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Among the patients listed for LT in the study by Karvellas et al (6) (Supplemental Table 1), which represents a more homogeneous group than the overall cohort, those undergoing ICP monitoring did not show an increased mortality despite a lower rate of LT, suggesting a potential benefit of the measure. Consistent with prior studies, Karvellas et al (6,12) also found that patients with ICP monitoring received more ICP-directed therapies than those without. Knowing ICP values, therefore, provides valuable information for performing informed prognostic and therapeutic decisions in patients with ALF.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Among the patients listed for LT in the study by Karvellas et al (6) (Supplemental Table 1), which represents a more homogeneous group than the overall cohort, those undergoing ICP monitoring did not show an increased mortality despite a lower rate of LT, suggesting a potential benefit of the measure. Consistent with prior studies, Karvellas et al (6,12) also found that patients with ICP monitoring received more ICP-directed therapies than those without. Knowing ICP values, therefore, provides valuable information for performing informed prognostic and therapeutic decisions in patients with ALF.…”
supporting
confidence: 80%
“…Among 56 patients in the study by Karvellas et al (6) who had ICP monitoring and complete complication data, four (7%) of them presented hemorrhagic complications (three intracranial, one spinal), three of which were fatal. ICP monitoring unnecessarily exposes patients who would never show increased ICP (-49% in the study by Karvellas et al 6]) to hemorrhagic complications; the "primum non nocere" principle, however, can also be applied for the misdiagnosis and mistreatment of intracranial hypertension that is assumed without ICP monitoring.…”
mentioning
confidence: 94%
“…Blood products were given less frequently over time, possibly as the deleterious effects of unnecessary blood transfusion in intensive care (15) and the futility of routine use and overuse of plasma administration in ALF (16) became better appreciated. Although the prevalence of patients with advanced encephalopathy remained unchanged, we observed less reliance on intracranial pressure monitoring during the later period, which may reflect concern over its limited clinical utility and associated risks (17, 18). The increased prophylactic use of antibiotics seen in the later period preceded the recognition (19) that this therapy does not seem to reduce bloodstream infections in ALF.…”
Section: Discussionmentioning
confidence: 81%
“…This quantitative imaging data combined with knowledge of corresponding neurologic function and response to therapy at prior time points may help the physician identify instances of neurologic deterioration with potential to benefit from cerebral edema directed therapies. The contentious role of ICP monitoring in hepatic encephalopathy management (3, 10, 16), failure of studies to show a benefit of invasive ICP monitoring and an association with worse outcome in some patients with liver failure (3, 10), and a large clinical trial that showed equivalence of invasive monitor-guided therapy to therapy guided by surveillance neurologic exams and neuroimaging in traumatic brain injury (29) suggest that there may be a growing role for non-invasive approaches to evaluating disease evolution in select patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, ICP change is an indirect measure of volume change and because CSF displacement to the spinal subarachnoid space has a buffering effect it is possible for cerebral edema to progress without clearly pathologic ICP elevation (4). Furthermore, invasive ICP monitoring is controversial in hepatic encephalopathy management because of the potential hemorrhagic complications of monitor placement, failure of several studies to identify a survival benefit, and recent evidence that invasive monitoring may be associated with worse outcome for some patients (3, 10). Additionally, the subdural and intraparenchymal ICP monitors most commonly used in liver failure may not accurately reflect compression of brain structures, such as the thalami and brainstem, distant from the device’s pressure transducer (11).…”
mentioning
confidence: 99%